Glycemic control and complications of type 2 diabetes mellitus in children and adolescents during the COVID-19 outbreak - Kyeong Eun Oh; Yu Jin Kim; Ye Rim Oh; Eungu Kang; Hyo-Kyoung Nam; Young-Jun Rhie; Kee-Hyoung Lee (Korean Society of Pediatric Endocrinology, 2023)
Purpose This study aimed to investigate the impact of coronavirus disease 2019 (COVID-19) on type 2 diabetes mellitus (T2DM) in children and adolescents. Methods Children and adolescents diagnosed with T2DM who visited the Korea University Hospital in 2019 and 2020 were retrospectively analyzed, including changes in body mass index (BMI)-standard deviation score (SDS), glycated hemoglobin (HbA1c), diabetes complications, and diabetes management from 2019 to 2020. Results Patient mean age and disease duration were 15.48±2.15 and 2.56±1.51 years, respectively. Obese patients accounted for 70.6% of the study population. From 2019 to 2020, mean BMI-SDS (2.21±1.25 vs. 2.35±1.43, P=0.044), HbA1c level (6.5%±2.72% vs. 7.3%±3.70%, P<0.001), blood pressure (BP), total cholesterol, and non-high-density lipoprotein cholesterol level in all patients increased significantly. Obesity was an independent predictor of increased HbA1c (95% confidence interval, 1.071-50.384; P=0.042). HbA1c levels did not increase significantly in nonobese patients, whereas HbA1c (6.45%±2.30% vs. 7.20%±3.05%, P<0.001), BMI-SDS (2.88±0.75 vs. 3.08±0.98, P=0.045), diastolic BP (P=0.037), and total cholesterol values (P=0.019) increased in obese patients in 2020 compared to 2019. Conclusions During the COVID-19 outbreak, glycemic control and diabetic complications worsened in children and adolescents with T2DM, particularly in obese patients. Close monitoring for glycemic control and diabetic complications is necessary in children and adolescents with T2DM, especially those with obesity.